Monitoring grassland degradation and restoration using a novel climate use efficiency (NCUE) index in the Tibetan Plateau, China. (November 2021) - An, Ru; Zhang, Ce; Sun, Mengqiu; Wang, Huilin; Shen, Xiaoji; Wang, Benlin; Xing, Fei; Huang, Xianglin; Fan, Mengyao
Highlights: Propose a NCUE index for monitoring grassland dynamic to reduce climate fluctuation. NCUE is suitable for cold and dry climate characteristics of Tibetan Plateau, China. Construct an Integrated Meteorological Factor (IMF) Reveal the spatio-temporal characteristics of grassland change from 1982 to 2012. NCUE can mitigate the impact of climate fluctuation and reflect grassland changes. Abstract: Grassland degradation is one of the most pressing challenges in natural environment and anthropogenic society. However, there is yet no effective approach for monitoring the spatio-temporal pattern of large-scale grassland degradation. In particular, the research on grassland changes in the harsh natural environment such as the Qinghai-Tibet Plateau is still in its infancy due to complexity, and it is extremely difficult for humans to reach these remote areas. The annual changes in the grassland biomass might be the results of climate fluctuations or grassland degradation. To test the hypothesis, the impact of inter-annual climate fluctuations needs to be considered when monitoring the grassland degradation based on spatio-temporal change of grassland biomass. In this paper, we propose a Novel Climate Use Efficiency index (NCUE) by considering rainfall, temperature, sunlight time, wind speed, surface temperature, accumulated temperature, time lag effect, light, temperature and water suitability and their coordination climatic factors that mainly affect vegetation growth comprehensively, to monitor grassland change suitable for cold and dry climate characteristics of the Qinghai-Tibet Plateau, and to reduce the effect of inter-annual variability of grassland productivity caused by climate fluctuation. As a consequence, grassland degradation monitoring could be more accurate and objective than existing ecological indicators. Our experiments show that the slope of NCUE over 31 years from 1982 to 2012 is 0.0028, showing a recovery trend in grassland. Degradation and restoration of grassland exist at the same time, and their proportions are 20.49% and 23.89%, respectively. By comparing with in-situ measurements in 2013 and 2009, 68% consistency was achieved with our prediction, and the 70% consistency is achieved by comparing with the positive and negative change trend of accumulated NDVI during the growing season. Moreover, the comparative analysis of land use/cover changes (LUCC) from 1990 to 2010 shows 69% of consistency. The ratio of the area of grassland significantly degradation and recovered predicted by NCUE change trend is 1.41% and 1.43%, respectively. It occupies a very small area of the study area. Yet, that predicted by NDVI change trend is 42.17% and 31.90%, respectively, and about 70% of the area is detected as drastic changes. It shows that NDVI is sensitive to climate fluctuations, while NCUE reduces the impact of climate fluctuations, reflecting change of grassland being affected by human activities and long-term climate change. The novel NCUE has great potential and utility to minify the impact of climate fluctuation and reflect grassland changes over space and time quantitatively. Such ecological index provides a new understanding of spatial and temporal patterns of grassland degradation in the Three River Headwaters Region (TRHR) at the same time.